Development of islamic guidance and counseling program for bullying prevention in MTS - Iim Imaroh; Imas Kania Rahman; Rahmat Rosyadi; Nida Rafiqa Izzati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
One of the social problems in the world of education is bullying. Bullying often occurs in school environments, including in Madrasah Tsanawiyah (MTs). In the context of Islamic education, bullying behavior is very contrary to Islamic values ​​that teach about tolerance, compassion, respect for others, and avoiding cruel acts. The increasing cases of bullying in educational environments indicate the need for more effective prevention efforts. This study aims to develop a guidance and counseling program based on Islamic values ​​to prevent bullying in Madrasah Tsanawiyah (MTs). This program is expected to strengthen the role of guidance and counseling (BK) teachers in educating and guiding students to prevent bullying behavior in the school environment. This study uses a research and development (R&D) method with the ADDIE model approach which includes five stages: analysis, design, development, implementation, and evaluation. At the field needs analysis stage, needs identification was carried out through BK teachers from various regions in Indonesia using a questionnaire distributed online. The design stage is an initial prototype which will later be continued with a development stage that is validated by three experts including language experts, Islamic religious education experts, and Islamic guidance and counseling experts. The development process continued with implementation testing on 10 BK teachers to assess the effectiveness and suitability of the program in the field. The final stage was an evaluation conducted with feedback from experts to refine the program. The results of the study showed that BK teachers at the MTs/SMP level really needed a structured Islamic guidance and counseling program for bullying prevention. This program was proven effective after going through the validation process and implementation test, where BK teachers stated that this approach had a positive impact on reducing bullying behavior among students. In addition, the results showed that the implementation of this program can have a long-term positive impact, both in building better student character and creating a safer and more conducive school environment. This study recommends strong collaboration between teachers, parents, and other education stakeholders to ensure the successful implementation of the bullying prevention program. In addition, it is recommended that other researchers explore other bullying prevention approaches that are appropriate to the cultural context and religious values ​​at various levels of education.